Процедура розв'язання задачі управління структурою інвестиційного портфеля фізичної особи - Голоскоков, Олександр Євгенович; Крюков, І. Д. (НТУ "ХПІ", 2014)
Пропонується підхід до управління структурою інвестиційного портфеля фізичної особи, в рамках якого потрібно визначити оптимальну стратегію управління інвестиційним портфелем шляхом знаходження ризикової структури портфеля і розподілу капіталу між різними видами активів. Розглядається одна з основних портфельних теорій – модель Марковіца, яка є фундаментальною у теорії портфельних інвестицій.

An approach to the management structure of the investment portfolio of an individual, in which you need to determine the optimal strategy for managing the investment portfolio by finding the risk structure of the portfolio and capital allocation between different types of assets. Considered one of the main portfolio theory - Markowitz model, which is fundamental in the theory of portfolio investments and is used when the structure of the risk portfolio. In the allocation of capital between risk and risk-free part of the portfolio management is used in the form of feedback based on the Pontryagin maximum principle. The allocation of capital between the different types of investments carried out in such a way that the real capital of the portfolio should be a capital investor specified benchmark portfolio with a given yield to them.
The procedure for solving the control problem of the investment portfolio structure for an individual person
Keywords: портфельне інвестування; інвестиції; інвестиційний портфель; активи; ризики; акції; банківські вклади; фізична особа; investment portfolio management; assets; risks; stocks; bank deposits